PERFORMANCE ANALYSIS OF FIXED PHOTOVOLTAIC SOLAR PANELS WITH 150° AND 30° TILT ANGLE VARIATIONS - M.Zakarsyi Lilma Abid; Alviani Hesthi Permata Ningtyas (Department of Mechanical Engineering, Universitas Sultan Ageng Tirtayasa, 2026)
Solar energy is a type of renewable energy that can be turned into electricity through the use of solar panels that capture sunlight. Solar panels work best when they are positioned at the right angle to catch as much sunlight as possible. One important thing that affects how well they work is how tilted they are compared to the sun's position in the sky. This study is meant to look at how well solar panels work statistically when they are tilted at 30 degrees and 150 degrees. The research employed an experimental method by directly measuring voltage, current, output power, and light intensity on the solar panels. Data collection was conducted for 8 days from 08:00 to 16:00 WIB. The monitoring system utilized INA219 sensors to measure electrical parameters and BH1750 sensors to measure light intensity, integrated with an ESP32 microcontroller based on the Internet of Things (IoT). The results indicate that differences in tilt angle affect the amount of solar radiation received by the panel, which consequently influences the electrical energy produced. The solar panel with a 150° tilt angle demonstrated better performance because it received more optimal sunlight exposure, particularly from morning to midday. This condition resulted in higher voltage, current, power, and electrical energy output compared to the panel with a 30° tilt angle. Based on the calculations, the 150° tilt angle increased power and energy generation by 25.38% compared to the 30° tilt angle during the testing period. Therefore, the tilt angle of a solar panel significantly affects the overall performance of a solar energy system.